OH, MSA, and H2SO4 measurements during OASIS Barrow field intensive Spring 2009 (Arctic Data Center, 2016)
A measurement intensive campaign was carried out in Barrow, Alaska, in spring 2009 as part of the Ocean Atmosphere Sea Ice Snowpack (OASIS)program. This dataset contains OH, methane sulfonic acid (MSA), and H2SO4 measurements.